The historical performance of music : an introduction - Lawson, Colin (Colin James) (Cambridge handbooks to the historical performance of music., 1999)
This volume offers an overview of historical performance, surveying current issues, and suggesting future developments. Its kernel comprises discussion of the performer's primary source-materials and their interpretation, aspects of style and technique that combine to make up a well-grounded, period interpretation, and a survey of performance conditions and practices.